Modulation of strain on electronic structure and contact type of BP/SnS van der waals heterostructure. (24th December 2021) - Chen, Jia-Le; Du, Jing-Xue; Yang, Jing; Shi, Li-Jie
Abstract: Vertical van der Waals heterostructures (vdWH) composed of two monolayer (ML) materials can provide new opportunities for layered electronic devices. Here we present a detailed theoretical investigation about the electronic properties of BP/SnS vdWH by applying in-plane uniaxial and biaxial strains. Our first principles calculations suggest that the direct bandgap of BP/SnS vdWH can be maintained within a large range of uniaxial and biaxial strains. We also find that the bandgap, band alignment and contact type of BP/SnS vdWH can be tuned by uniaxial and biaxial strains. In addition, the Poisson's ratio exhibits an intense anisotropy with respect to the uniaxial strain along zigzag (ZZ) and armchair directions. The easily tunable electronic properties and highly anisotropic character of BP/SnS vdWH make it to be a promising material in the field of photovoltaic cells, photodetectors, and other functional nano devices.